1998
DOI: 10.1021/jp980690h
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition of Dimethyl Methylphosphonate (DMMP) on Alumina-Supported Iron Oxide

Abstract: The adsorption of dimethyl methylphosphonate (DMMP) on alumina-supported iron oxide has been examined. DMMP reacts on adsorption at room temperature, apparently through cleavage of the phosphorus−carbon bond. This bond is observed to be extremely resistant to cleavage when DMMP is adsorbed on oxides such as alumina, magnesia, and lanthana. The phosphorus−methoxy bonds, which are the most readily cleaved on the other oxides, appear at least initially to remain intact on the alumina-supported iron oxide. The hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
82
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(88 citation statements)
references
References 15 publications
(37 reference statements)
3
82
0
Order By: Relevance
“…Several studies were carried out to understand the mechanism of the adsorption and decomposition processes on such oxides as alumina-supported cerium oxide and iron co-impregnated oxide [31], manganese oxide [32], monoclinic tungsten oxide (m-WO 3 ) [33], cerium oxide, Fe 2 O 3 , silica [34][35][36][37][38], and TiO 2 [39][40][41][42]. The thermal oxidative decomposition study of DMMP on amorphous manganese oxide and Al 2 O 3 -supported manganese oxide catalyst has shown the DMMP oxidation to CO 2 [32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies were carried out to understand the mechanism of the adsorption and decomposition processes on such oxides as alumina-supported cerium oxide and iron co-impregnated oxide [31], manganese oxide [32], monoclinic tungsten oxide (m-WO 3 ) [33], cerium oxide, Fe 2 O 3 , silica [34][35][36][37][38], and TiO 2 [39][40][41][42]. The thermal oxidative decomposition study of DMMP on amorphous manganese oxide and Al 2 O 3 -supported manganese oxide catalyst has shown the DMMP oxidation to CO 2 [32].…”
Section: Introductionmentioning
confidence: 99%
“…DMMP on the alumina-supported cerium oxide decomposes by producing methanol and dimethyl ether [34]. DMMP adsorbs on iron oxide at room temperature through cleavage of the phosphorus-carbon bond [35]. The phosphorus-methoxy bonds appear at least initially to remain intact on the alumina-supported iron oxide.…”
Section: Introductionmentioning
confidence: 99%
“…175 Despite the lower surface area (18.3 m 2 /g) of the quasicubic ␣-Fe 2 O 3 than the flower-like one (39.9 m 2 /g), the superior performance of the cubes was attributed to the exclusive exposure of the {110} planes that had a much higher iron density (10.1 atoms/nm 2 ), facilitating the activation of CO. ␣-Fe 2 O 3 nanorods showed exceptionally high activity in CO oxidation and CH 4 combustion because of the preferentially exposed {110} planes. 260, 261 Such kind of shape-dependent catalytic behavior of ␣-Fe 2 O 3 has also been identified in liquidphase reactions [262][263][264][265] and photocatalysis. [266][267][268][269] Similar size and shape effects on the catalytic properties of ␥ -Fe 2 O 3 nanomaterials were also observed.…”
Section: Fe 2 O 3 Nanocatalystsmentioning
confidence: 95%
“…5 In subsequent experiments, Mitchell reported that the addition of cerium oxide to Fe 2 0 3 /alumina increased the decomposition yield of DMMP, and that alumina-supported CeO 2 /alumina was even more reactive. Analysis of the CeO 2 phase determined that the yield of reaction products was a result of amorphous and not crystalline CeO 2 .…”
Section: Introductionmentioning
confidence: 98%